Effects of Fe3+ on Acute Toxicity and Regeneration of Planarian (Dugesia japonica) at Different Temperatures. (22nd August 2019) - Ding, Xue; Song, Linxia; Han, Yahong; Wang, Yingbo; Tang, Xiaowang; Cui, Guicai; Xu, Zhenbiao
Abstract : Objective . To investigate the effects of different concentrations of Fe 3+ on the acute toxicity and regeneration of planarian at different temperatures. Method . The planarians were treated with 40 mg/l, 50 mg/l, 60 mg/l, and 70 mg/l Fe 3+ solution and placed in 15°C, 20°C, and 25°C, respectively, to observe the mortality and the poisoning pattern of the planarian. In addition, the planarians were cut into three parts of head, trunk, and tail, then placed in Fe 3+ solution at concentrations of 10 mg/l, 15 mg/l, 20 mg/l, and 30 mg/l, and placed in 15°C, 20°C, and 25°C respectively, and the regeneration rate of the planarian was investigated. Results . At the same temperature, in the concentration of Fe 3+ from 40 mg/l to 70 mg/l, the mortality of the planarian increased with the increasing of the concentration of Fe 3+ ; at the same concentration and different temperatures, the death speed of the planarian is the fastest at 20°C, the next at 25°C, and the lowest at 15°C, indicating that the toxic effect of Fe 3+ can be accelerated at a suitable temperature of 20°C. At the same temperature, in the low concentration of Fe 3+ from 10 mg/l to 30 mg/l, the regeneration rate of the planarian gradually decreased with the increasing of the concentration of Fe 3+ ; at the same concentration and different temperature, the regeneration rate of planarian was faster at 20°C and 25°C, but the difference between 20°C and 25°C was small, and the slowest at 15°C, indicating that the low temperature significantly affects the planarian regeneration speed. The study also found the regeneration rates of the head, trunk, and tail of the planarian were different; the head regeneration was the fastest, the trunk was the second, and the tail was the slowest. Conclusion . Fe 3+ had obvious toxic effects on the survival and regeneration of planarian; the planarian is sensitive to Fe 3+ and may be used to detect Fe 3+ water pollution; in addition, temperature can affect the toxic effects of Fe 3+ and thus affect the survival and regeneration of the planarian. Therefore, the temperature should be taken into consideration when detecting water Fe 3+ pollution.